Obstacles and Solutions in Law Enforcement Against the Crime of Electronic Data and Information Falsification - Faisal Santiago; Endro Satoto (CV. Publikasi Indonesia, 2024)
The criminal act of falsifying data via the internet is included in the category of cybercrime and still faces obstacles in law enforcement. The formulation of the problem in this research is about the factors that cause criminal acts of falsifying information data and electronic transactions, law enforcement against perpetrators of criminal acts of falsifying information data and electronic transactions, as well as the obstacles faced in law enforcement against perpetrators of criminal acts of falsifying information data and electronic transactions, and how to overcome them. The author uses an empirical juridical approach, using primary and secondary data. Data analysis uses qualitative analysis. The research results show that: Law enforcement against perpetrators of criminal acts of falsifying information data and electronic transactions is divided into three, namely preemptive, preventive, and repressive. The obstacles faced in law enforcement against perpetrators of criminal acts of falsifying information data and electronic transactions are divided into internal obstacles, namely the limited number of investigators, high operational costs, and lack of optimal coordination between the police and other related parties. Meanwhile, external obstacles include the lack of evidence obtained from the victim, the majority of witnesses not knowing who the person was, when, what they were using, and the reason the account was created, and a lack of legal awareness from the public.